FISH IDENTIFIER: MOBILE APPLICATION TO RECOGNIZE FISH IN MARKETPLACE USING IMAGE PROCESSING AND MACHINE LEARNING WITH INVENTORY MANAGEMENT SYSTEM - AHMAD ZAHIRI, AHMAD SYAHIR (IRC, 2019)
Going to the wet market become a normal task for most consumer nowadays. Fish are one of the main products that can be found in the wet market and commonly targeted by the consumer. However, lack in description of the fish affects the behavior in buying the goods. The buyer will ask the seller regarding the details of the fish and cause buying and selling session to become longer. To overcome this problem, the usage of image processing, machine learning and blockchain comes into place to detect the fish and get the details such as name, price and available quantity. This paper exposes on developing a mobile application embedded with these technologies as a platform to ease the consumer and seller in the market.